CLINICAL STUDY ON THE USEFULNESS OF LAPAROSCOPIC APPENDECTOMY - TAKASE, Yasuhiro; SHIBUYA, Susumu; CHIKAMORI, Fumio (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2000)
The usefulness of laparoscopic appendectomy (LA) was studied in terms of its need assessment based on exploratory therapeutic results and a questionnaire survey. Subjects were 62 cases undergone LA at the hospital from October 1997 to August 1999. Their ages ranged from 7 to 81 years. LA using three trocars was employed, and a 10/12mm trocar to the umbilical region, a 5/7mm trocar to the right flank, and a 5/7mm trocar to the superior extremity of the pubis were inserted. Mesentery and the root of the appendix were ligated in the body with 1-0 silk thread, and then the appendix was resected by mean of ultrasonic coagulotomy. As a result, the ratio of converting to laparotomy was 3.2%. Mean operating times were 98±38 min (n=15) in gangrenous appendicitis and 65±18 min (n=15) in non-gangrenous appendicitis (p<0.01). Complications included bleeding at the sites of inserting trocars in one case and intraabdominal abscess in one case in the early time of the study. A questionnaire survey revealed that 89.0% of the subjects answered preferably to select LA than laparotomic appendectomy. It is concluded that LA is an established technique and is benificial in cosmetic merit as well as in the differential diagnosis of gynecological emergency disorders. In the explanation of operative procedures for appendectomy, we must explain LA to pay respect to the patient's right to choice the therapeutic method.